Synthesis and characterization of curcumin-phosphatidylcholine complex via solution enhanced dispersion by supercritical CO2 - Vuong, Phan Minh; Ty, Nguyen Minh; Thanh Tung, Pham Cao; Thao, Phan Thanh (Vietnam Journal of Chemistry, 2017)
In order to enhance the bioavailability of poorly water-soluble curcumin, solution enhanced dispersion by supercritical carbon dioxide (CO2) (SEDS) was employed to prepare curcumin-phosphatidyl choline complex. The reaction parameters were varied and investigated. The typical parameters were determined as follow: P = 200 bar, T = 60 °C, gas flow rate 10 mL.min-1, molar ratio of phosphatidylcholine:curcumin 2:1, ratio of dichloromethane/scCO2 15 % (w/w). The characteristics of complexation product were measured such as the water solubility, natural stability, UV-Vis, FTIR and DSC. The FE-SEM image shows that curcumin-phosphatidylcholine complex appeared in two types of spherical shape with the big particle size of complex approximately 0.9 µm and nano curcumin with particles size of approximately 100 nm. This study revealed that supercritical CO2 technologies had a great potential in fabricating complex and improving the bioavailability of poorly water-soluble drugs. Keywords. Curcumin, water soluble curcumin, phosphatidylcholine, CO2 supercritical fluids.